The power of unearned suffering : the roots and implications of Martin Luther King, Jr.'s theodicy - Edmondson, Mika (Religion and race, 2017)
This book represents the first systematic study of King's doctrine of redemptive suffering, a central tenet of his theology. It explores the roots and contemporary relevance of King's redemptive suffering theodicy and answers his recent black humanist and womanist critics.